Assessment of genetically modified maize Bt11 × MIR162 × MIR604 × 1507 × 5307 × GA21 and subcombinations, for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐DE‐2011‐103). (5th April 2019) - ,; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: Maize Bt11 × MIR162 × MIR604 × 1507 × 5307 × GA21 (six‐event stack maize) was produced by conventional crossing to combine six single events: Bt11, MIR162, MIR604, 1507, 5307 and GA21. The GMO Panel previously assessed the six single events and 22 of their combinations and did not identify safety concerns. No new data on the maize single events or their 22 combinations that could lead to modification of the original conclusions on their safety have been identified. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological, allergenicity and nutritional assessment indicate that the combination of the single maize events and of the newly expressed proteins in the six–event stack maize does not give rise to food and feed safety and nutritional concerns. The GMO Panel concludes that the six‐event stack maize, as described in this application, is as safe as and nutritionally equivalent to its non‐GM comparator and the non‐GM reference varieties tested. In the case of accidental release of viable grains of the six‐event stack maize into the environment, this would not raise environmental safety concerns. The GMO Panel assessed the likelihood of interactions among the single events in the 34 maize subcombinations not previously assessed and concludes that these are expected to be as safe as and nutritionally equivalent to the single events, the previously assessed subcombinations and the six‐event stack maize. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of the six‐event stack maize. Post‐market monitoring of food/feed is not considered necessary. The GMO Panel concludes that the six‐event stack maize and its subcombinations are as safe as its non‐GM comparator and the tested non‐GM reference varieties with respect to potential effects on human and animal health and the environment.